2017
DOI: 10.1039/c7dt02073b
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of mesoscopic compounds of cetyltrimethylammonium and Keggin metatungstates

Abstract: A hybrid surfactant/polyoxometalate compound was synthesized by combining isopolytungstate anions with the cationic surfactant cetyltrimethylammonium bromide (CTA-Br) to produce a hierarchical compound that we identify as (CTA)[HWO]Cl·2HO. At room temperature the compound consisted of hexagonally ordered sheets of Keggin ions, with an intervening gallery containing alkyl-chains of the organic cations. The synthesis was highly dependent on solution pH, reaction time and the order in which the reactants were add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…The peak at d ¼ 9.80Å is assigned to diffraction between Keggin ions within each plane. 21 Previous work has shown that two Keggin ions in a unit cell with a ¼ 12.40 AE 0.10Å, b ¼ 16.45 AE 0.10Å, c ¼ 24.90 AE 0.20Å, a ¼ 90 , b ¼ 101.5 AE 0.5 and g ¼ 90 will produce a diffraction pattern similar to that observed. 21 The peaks at 24.5Å and 9.80 A correspond to (001) and (110) respectively if indexed on the above unit cell.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…The peak at d ¼ 9.80Å is assigned to diffraction between Keggin ions within each plane. 21 Previous work has shown that two Keggin ions in a unit cell with a ¼ 12.40 AE 0.10Å, b ¼ 16.45 AE 0.10Å, c ¼ 24.90 AE 0.20Å, a ¼ 90 , b ¼ 101.5 AE 0.5 and g ¼ 90 will produce a diffraction pattern similar to that observed. 21 The peaks at 24.5Å and 9.80 A correspond to (001) and (110) respectively if indexed on the above unit cell.…”
Section: Resultssupporting
confidence: 52%
“…An interplanar distance of 24.5Å was also measured using low-angle powder XRD. 21 The length of one CTA + surfactant ion is reported to be 24Å, 41 and the metatungstate anion has a diameter of 10Å, 42 indicating that a signicant degree of interdigitation of the CTA + tailgroups occurs within the structure. In a related POM structure, 38 (CTA) 5 (CH 3 CN) 4 [H x SiMo 12 O 40 ], the CTA + tail groups were interdigitated by an average of 13.3 carbons per chain with some CTA + cations completely interdigitated (16 carbons) and others only by 9 carbons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of (C 19 H 42 N) 7 Cl[H 2 W 12 O 42 ] 2H 2 O (designated in this work as CTA‐W 12 ) has been described elsewhere . X‐ray photoelectron spectroscopy measurements were conducted using a Thermo Scientific ESCALAB250Xi, utilising monochromated Al K‐α (1486.68 keV) radiation at a power of 120 W (13.8 kV × 8.7 mA).…”
Section: Methodsmentioning
confidence: 99%